Thermal Properties of Perovskite-Type Oxides La0.6Sr0.4Co1-XFexO3-δ (0 ≤ x ≤ 1.0). (26th April 2016) - Shin, Yu-Cheol; Hashimoto, Shin-ichi; Yashiro, Keiji; Amezawa, Koji; Kawada, Tatsuya
Abstract : Perovskite-type oxides La0.6 Sr0.4 Co1-x Fex O3-δ (LSCF) have been prepared with Co contents of 0 ≤ x ≤ 1.0 by a Pechini method and characterized by X-ray diffraction analysis. Their thermal diffusivities were measured as a function of oxygen partial pressure ( P O2 ) in the temperature range between 873K and 1273K by a Laser Flash Method (LFA). Heat capacities were measured by TG-DSC@at heating rate 10K/min in the range of temperature between R.T and 1273K. The LSCFs thermal diffusivity was found to be a single function of oxygen deficiency, δ, independently of temperature as well as oxygen partial pressure and Co contents in intermediate temperatures range (873 to 1273K).